Prosopographical Datatabases in the Context of Modern Research in the History of Universities – Universitas Magistrorum (1358–1622) Database - Škudrnová, Jaroslava; Synovcová Borovičková, Jana (My University, 2020)
This article presents the online database being created as part of the project Universitas Magistrorum: Professors of the Utraquist University of Prague (1458–1622). It briefly outlines general development in the area of digital humanities and sets it in the context of other prosopographical projects.
Prosopografické databáze v kontextu moderního bádání o dějinách univerzit - databáze Universitas Magistrorum (1458–1622)
Keywords: digital humanities; prosopography; prosopographical databases; universities; university history; university professors; Prague University; the Middle Ages; the early modern period; digital humanities; prosopografie; prosopografické databáze; univerzity; dějiny univerzit; univerzitní profesoři; Pražská univerzita, středověk, raný novověk